PENGEMBANGAN E-LKPD IPA BERBASIS CATUR ASRAMA KELAS V - K. Tariani; I.W. Suastra; I.G. Astawan (PENDASI Jurnal Pendidikan Dasar Indonesia, 2022)
This study aims to develop a valid and readable E-LKPD IPA based on catur asrama for the fifth grade of elementary school in the first semester. This study uses the ADDIE development model, with the following stages: analysis, design, development, implementation, and evaluation. In this study, it was only limited to the development stage with considerations of urgency, time constraints, research budget, and the ability of researchers, especially because the first semester of science material had been studied while this research was carried out in the second semester. The subjects in this study were 9 students of class V SD Negeri 2 Lemukih. This research data collection uses a validation sheet for 3 lecturers and 3 educators and a readability sheet for 9 students. The instrument used in measuring the level of validity and readability of the E-LKPD is a validation and readability sheet containing a Likert scale 4. The data were analyzed descriptively to obtain the percentage of validity and the mean score of E-LKPD readability. The percentage of E-LKPD validity is 96% with a "very high validity" level of validity and an average E-LKPD readability score of 3.9 with a "very good" readability level. Based on the results of data analysis, the E-LKPD IPA based on catur asrama for the fifth grade of elementary school in the first semester which is valid and tested for readability is suitable for use as teaching materials in learning for teachers and students in elementary school.